Effect of building direction and heat treatment on the wear behavior of H13 tool steel processed by laser powder bed fusion - Adriel P. Oliveira; Tales Ferreira; Reginaldo T. Coelho; Claudemiro Bolfarini; Piter Gargarella (Journal of Materials Research and Technology)
Components such as molds and dies face the challenge of costly preparation due to their complex geometry. However, Additive Manufacturing offers unprecedented design freedom for these tools. In this study, AISI H13 hot work tool steel was processed by laser powder bed fusion (L-PBF) and subjected to reciprocal wear tests against Al2O3 pin in a sphere-on-plate configuration to evaluate its wear behavior. Comparative analyses were conducted with the same material processed by arc melting (560HV). The microstructure of the printed H13 revealed a cellular morphology, characterized by martensite cells enveloped in retained austenite (556HV). This microstructure was transformed into tempered martensite after heat treatment, maintaining the hardness in the same range (547HV). As-printed samples exhibited a Coefficient of Friction (COF) between 0.72 and 0.85, while heat-treated samples showed a reduced range of 0.72 < COF <0.76. The specific wear rate showed a slight variation between different building directions in the as-printed conditions, with values of 1.7 × 10^−4 and 1.2 × 10^−4 mm³/N·m for perpendicular and parallel directions to the building direction, respectively. These wear rates were marginally inferior to conventionally processed material (2.2 × 10^−4 mm³/N·m). Notably, the printed sample with post-hardening heat treatment exhibited the highest wear rate (3.0 × 10^−4 mm³/N·m) compared to as-printed and arc-melted counterparts. Across all conditions, abrasion, adhesion, and delamination were identified as the prevalent wear mechanisms. The findings emphasize the feasibility of manufacturing H13 parts with complex geometries while preserving excellent wear properties, even prior to thermal treatment.